IN SEARCH OF HISTORY AS MEMORY: EDITORIAL COMMENT (Historia, 2021)
For many a late twentieth century historian it is difficult to understand at all times precisely which thought processes were responsible for intellectual revolutions in the modern history of the world. This may be a result of the fact that we tend to merely take for granted that with which we are preoccupied. The historical transformations of memory is a good example.
Keywords: Historia; Volume 43 No. 2; historical transformations; memory; Hutton; Simon Schama; Landscape and Memory; history